Application of disposable digital hysteroscope for outpatient hysteroscopy in women undergoing artificial assisted reproductive procedures: a clinical research - Limin Feng; Resad Pasic; Jianming Song; Adel Shervin; Die Jiang; Ling Dan (BMJ Publishing Group, 2024)
Background Hysteroscopy is the preferred method for the diagnosis and treatment of uterine diseases. With the increasing demand for outpatient hysteroscopy, disposable digital hysteroscopy has emerged, which can meet the requirements of diagnosis and treatment integration, and greatly reduce the labour and storage costs.Methods A total of 108 outpatients who underwent hysteroscopy using disposable digital hysteroscope were divided into two groups: the non-porous group (group A, n=49) and the married with child group (group B, n=59). The patients' general information and clinical data were recorded and statistical analysis was performed.Results No differences were found between the age, weight, body mass index, menopausal status and indication for hysteroscopy of the two groups. The most common indication was embryo transfer failure. The surgical success rate of 108 patients was 100%, the concordance rate between hysteroscopic diagnosis of chronic endometritis and pathological diagnosis was 94.44% (68/72), while the false positive rate stood at 38.89% (14/36). Additionally, incidental findings rate for endometrial polyps was 92.00% (23/25) with a low false positive rate of only 6% (5/83). The mean visual analogue scale score of group A was 2.285±0.180, which was not significantly different from group B (p=0.483, 95% CI(−0.60-0.44)). The pregnancy rate among patients who received assisted reproductive technology and were followed up for 1 year after surgery was 66.67% (40/60), while the abortion rate stood at 5.00% (3/60).Conclusions The disposable digital hysteroscope is a valuable and effective tool for outpatient hysteroscopy.